Isoquinolinium Dichromate and Chlorochromate as Efficient Catalysts for Oxidative Halogenation of Aromatic Compounds Under Acid-Free Conditions. Issue 6 (2nd June 2016) - Rao, A. Sambashiva; Rajanna, K. C.; Reddy, K. Rajendar; Kulkarni, Subhash
Abstract : Isoquinolinium dichromate and isoquinolinium chlorochromate were found as efficient catalysts to trigger oxidative bromination and iodination of aromatic hydrocarbons with KBr/KI and KHSO4 under acid-free conditions. Reaction times reduced highly significantly under sonication, followed by corresponding mono bromo derivatives in very good yield with high regioselectivity.